Perancangan Aplikasi Multimedia Untuk Pembelajaran Gerbang Logika Menggunakan Augmented Reality - Rosdelima Hutahaean; R. Rizal Isnanto; Kurniawan Teguh Martono (Jurnal Teknologi dan Sistem Komputer, 2015)
As the rapid development of technology is also growing media that is used as a method of learning in education. One of them to learning logic states, in addition to reading the book at this time there has a new learning method that is more pronounced in 3 dimensions to increase understanding in learning the logic gates using Augmented Reality. Steps design multimedia for learning the logic gates begins with a literature study, data collection, analysis and system design and then implementation and testing the system. Testing methods using a black-box, which includes testing functionality testing camera angles and distances to the markers as well as testing the light intensity. The result of the design this application shows that for angle of 30 0 with a distance of 30 cm – 40 cm, angle of 45 0 with a distance of 40 cm – 70 cm and angle of 60 0 with a distance of 50 cm – 90 cm and light intensity 4 lx – 19 lx is a good composition can display the object 3 dimensions.